Risky Casual Sex and Posttraumatic Stress in College Females: An Examination of Assault History, Self-Esteem, and Social Support - Kennedy, Seigie (Violence against women, 2021)
Casual sex, although common in college culture, can increase the risk of sexual victimization, which in turn can lead to posttraumatic stress disorder (PTSD). This study examined sexual victimization, self-esteem, and social support as relative predictors of PTSD and risky casual sex (RCS) in a sample of 229 female undergraduates. Results suggested that enhancing self-esteem may have a greater relative impact on PTSD symptoms compared with social support, even after accounting for the impact of sexual victimization. Moreover, a reduction in PTSD symptoms may have the potential to minimize RCS. Future research is needed to determine temporal relations among these variables.